Effectiveness of The Kumon Method In Improving Mathematical Problem-Solving Abilities - Sastra, Dela Zelinka; Rahman, Andhika; W, Wahyunengsih (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to explore how effective the Kumon method is in enhancing students’ abilities to solve mathematical problems, based on an in-depth analysis of existing literature.  Employing thematic document analysis, three contemporary Indonesian scholarly articles were scrutinized to investigate the effects of the Kumon method on educational outcomes, autonomous learning practices, and logical reasoning abilities. The results show that the Kumon teaching methodology significantly improves students’ understanding of mathematical principles, enhances self-management skills and fosters an independent attitude in the learning environment, and improves academic achievement. Nevertheless, the inherent repetitive characteristics of the program and the constrained avenues for peer interaction may detrimentally influence students’ motivation and levels of engagement. Empirical data shows that although Kumon effectively develops basic mathematics skills, it is better to apply a learning approach that involves interaction and cooperation, so that learning is more tailored to the needs of each student. This finding has significant implications for educators and curriculum designers in formulating organized and student-centered mathematics teaching